2020
DOI: 10.1103/physrevapplied.13.024061
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline versus Amorphous Donor-Acceptor Blends: Influence of Layer Morphology on the Charge-Transfer Density of States

Abstract: Organic small molecule solar cells are used as a test bed to investigate the influence of film morphology on the density of charge-transfer (CT) states. CT states are considered as precursors for charge generation and their energy as the upper limit for the open-circuit voltage in organic donor-acceptor solar cells. In this study the influence of morphology for two perylene donors [crystalline diindenoperylene (DIP) versus amorphous tetraphenyldibenzoperiflanthene (DBP)] with almost identical ionization energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 46 publications
(80 reference statements)
2
72
1
Order By: Relevance
“…Our experimental observations on the other hand do not corroborate Kahle's claim on the strong influence of static disorder. We finally note the very recent manuscript by Linderl et al, 58 who observed a very similar behavior in DBP:C 60 devices as we have done herein.…”
Section: Explanation Of Negative Extrapolated Variance Values; a Multsupporting
confidence: 88%
“…Our experimental observations on the other hand do not corroborate Kahle's claim on the strong influence of static disorder. We finally note the very recent manuscript by Linderl et al, 58 who observed a very similar behavior in DBP:C 60 devices as we have done herein.…”
Section: Explanation Of Negative Extrapolated Variance Values; a Multsupporting
confidence: 88%
“…This type of broadening is referred to as dynamic disorder 13 . Whilst dynamic disorder is temperature ( T ) dependent, static disorder is not and T-dependent CT absorption or emission measurements have therefore often been used to differentiate them 11 , 14 17 . Using T-dependent measurements, recent studies by Ortmann, Vandewal, Deibel and co-workers 14 , 16 , 18 have suggested that static disorder is less important in OPV than dynamic disorder, but other studies have observed the opposite 9 , 11 , 15 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst dynamic disorder is temperature ( T ) dependent, static disorder is not and T-dependent CT absorption or emission measurements have therefore often been used to differentiate them 11 , 14 17 . Using T-dependent measurements, recent studies by Ortmann, Vandewal, Deibel and co-workers 14 , 16 , 18 have suggested that static disorder is less important in OPV than dynamic disorder, but other studies have observed the opposite 9 , 11 , 15 , 17 . Although this debate is still ongoing, there is a large amount of computational and experimental evidence that the CT-state energy is sensitive to the microstructure, composition, and interfacial properties of organic semiconductor blends 19 – 31 , and multiple CT states have also been observed in several studies 26 , 29 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations